The Influencing Factors Of Decision Makers’ Behavioural Into Involvement In Public-Private Partnership (Ppp) Toll Expressway Projects In Malaysia - Syaromi Ramli
In emerging economies, Public Private Partnership (PPP) is a popular mechanism for the governments to meet the increasing national demand for the development of infrastructure, and provision of services and facilities such as expressways, ports and healthcare. Malaysia acknowledges the potential of PPP in delivering high-quality infrastructure and services to the general public. However, active involvement of the private sector in PPP toll expressway projects also presents a significant challenge to the government’s sustainable development programme and its inspiration to formulate a winning engagement with the private sector as the front runner and main engine of growth for the country’s economy. Many studies have been reported on PPP but very few on the influencing factors that affect the behavioural intentions and actions among the decision-makers in the private sector to participate in PPP, particularly in toll expressway projects. To bridge this gap, two (2) theoretical models, namely the Social Exchange Theory (SET) and Theory of Planned Behaviour (TPB) have been tested as the foundation to study and explain the characteristics of the empirical data collected from the decision-makers of toll concessionaires’ companies. A total of 352 practitioners and professionals (who were decision makers from the top and middle management) from twenty-six (26) toll concessionaire companies were sampled (using a stratified random sampling process). In the initial theoretical model, a total of eight (8) constructs were proposed and examined, namely; (a) attitude on PPP, (b) subjective norms, (c) perceived behavioural control, (d) governmental influence, (e) project viability, (f) behavioural intention of the decision makers, (g) involvement behaviour and (h) trust as the moderating factor. Questionnaires on all the eight constructs were developed, adopted and adapted from various authors. Data were analysed and hypotheses tested using SPSS 23.0 and AMOS 23.0 approaches of structural equation modelling (SEM). The results revealed that attitude (a), perceived behaviour control (c) and governmental influence (d) are factors that influence behavioural intention, and that the latter had impacts on involvement. The results also show that trust (h) is a moderator in the relationship between behavioural intention and involvement. Meanwhile the factors subjective norm (b) and project viability (f) did not influence behavioural intention. Overall, this study offers three segment findings with regard to PPP toll expressway projects namely: a comprehensive view of the challenges they faced, the influencing factors for decision-makers’ intention to get involved, and the exploration of trust as an intensifying effect towards their involvement. Thus, these could provide inputs towards enhancing the current PPP policy and its governance mechanism, while encouraging the participation of the private sector to be the front-runner and engine of growth for the economy.